Acroangiodermatitis (pseudo-Kaposi's sarcoma) in an HIV sero-positive patient with syphilis and hepatitis C virus coinfection: clinical and dermatopathological features - Fred Bernardes Filho; Gustavo Martins; José Augusto da Costa Nery; Cecília Vianna de Andrade; Bernard Kawa Kac (Sociedade Brasileira de Dermatologia, 2014)
Acroangiodermatitis is an angioproliferative disease usually related to chronic venous insufficiency, and it is considered a clinical and histological simulator of Kaposi's sarcoma (KS). Immunohistochemistry is the suitable method to differentiate between these two entities. It reveals the following immunostaining profile: immunopositivity with anti-CD34 antibody is restricted to the vascular endothelium in acroangiodermatitis, and diffuse in the KS (endothelial cells and perivascular spindle cells); immunopositivity with anti-HHV-8 only in KS cases. We report the case of an HIV seropositive patient without apparent vascular disease, who presented violaceous and brownish erythematous lesions on the feet, and whose histopathology and immunohistochemistry indicated the diagnosis of acroangiodermatitis.